Solar cyclic activity over the last millennium reconstructed from annual 14C data (Corrigendum) - Usoskin, Ilya; Solanki, S. K.; Krivova, N.; Hofer, B.; Kovaltsov, G. A.; Wacker, L.; Brehm, N.; Kromer, Bernd (Astronomy and astrophysics, 2022)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics
Gesehen am 28.10.2022